2002
DOI: 10.1080/03014460110058971
|View full text |Cite
|
Sign up to set email alerts
|

Protein electrophoretic markers in Israel: compilation of data and genetic affinities

Abstract: In contrast to the conclusions of several previous studies, there was no evidence for close genetic affinities among the Jewish populations or for a Middle Eastern origin for most of them. Since the study is the first to use only the more reliable protein electrophoretic markers, and an appropriately comprehensive panel of non-Jewish populations, the results are regarded as the most reliable available to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 147 publications
0
10
0
Order By: Relevance
“…Whereas recent Y-chromosomal studies have identified a trend of genetic affinity among Jewish populations [12,15,18], most notably a shared group of haplotypes common in Jewish priests from different Jewish populations [16,52,53], past autosomal studies of multiple Jewish populations have been somewhat more equivocal regarding the clustering of Jewish populations separate from non-Jewish populations [13,14,17,19,54-56]. Recent genomic studies that have identified a component of distinctive ancestry for Jewish individuals have largely focused on Ashkenazi Jews sampled in the United States in relation to the broader European-American population [7-10], finding most recently that individuals with even partial Ashkenazi ancestry can be detected on the basis of principal components analysis [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas recent Y-chromosomal studies have identified a trend of genetic affinity among Jewish populations [12,15,18], most notably a shared group of haplotypes common in Jewish priests from different Jewish populations [16,52,53], past autosomal studies of multiple Jewish populations have been somewhat more equivocal regarding the clustering of Jewish populations separate from non-Jewish populations [13,14,17,19,54-56]. Recent genomic studies that have identified a component of distinctive ancestry for Jewish individuals have largely focused on Ashkenazi Jews sampled in the United States in relation to the broader European-American population [7-10], finding most recently that individuals with even partial Ashkenazi ancestry can be detected on the basis of principal components analysis [10].…”
Section: Resultsmentioning
confidence: 99%
“…Although several studies have supported a genetic affinity among most Jewish populations, potentially due to shared ancestry [11-16], others have suggested similarity between Jewish and non-Jewish populations as a result of some level of gene flow among groups [12,14,17-19]. The discovery of shared Y chromosomes common in separate Jewish populations from different geographic regions has strengthened the evidence for shared Jewish genetic ancestry, but as evidenced in the considerable attention given in Israel to the 2008 scholarly book "When and how was the Jewish people invented" [20], debate continues regarding the issue of whether separate Jewish populations have any deep shared genetic ancestry beyond that shared with non-Jewish groups.…”
Section: Introductionmentioning
confidence: 99%
“…The first nine markers are polymorphisms of red cell enzymes and serum proteins, and were typed mostly by protein electrophoresis, but the variation at the protein level is directly related in a 1:1 manner to the SNP variation at the DNA level. Indeed, some of the results for the Jewish populations were obtained by PCR methods [1,14]. The polymorphism of the remaining eight markers can only be detected at the DNA level.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the studies, trying to establish the origins of the Jewish populations with autosomal markers, claimed that the Jewish populations have a common origin, but others concluded that the Jews are a very diverse group. This corpus of studies has already been critically reviewed [1]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation